2017
DOI: 10.1103/physrevfluids.2.074001
|View full text |Cite
|
Sign up to set email alerts
|

Imbibition with swelling: Capillary rise in thin deformable porous media

Abstract: The imbibition of a liquid into a thin deformable porous substrate driven by capillary suction is considered. The substrate is initially dry and has uniform porosity and thickness. Two-phase flow theory is used to describe how the liquid flows through the pore space behind the wetting front when out-of-plane deformation of the solid matrix is considered. Neglecting gravity and evaporation, standard shallow-layer scalings are used to construct a reduced model of the dynamics. The model predicts convergence to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…Recent work has, however, shown that a viscous term is crucially important in rapid mechanical dewatering tests on cellulose fibre suspensions at relatively large solid fractions [16]. Similar conclusions have been drawn from experiments involving the deformation of hydrogel spheres suspended in water [17,18] or during capillary imbibition of water in paper sheets [19].…”
Section: Introductionsupporting
confidence: 54%
“…Recent work has, however, shown that a viscous term is crucially important in rapid mechanical dewatering tests on cellulose fibre suspensions at relatively large solid fractions [16]. Similar conclusions have been drawn from experiments involving the deformation of hydrogel spheres suspended in water [17,18] or during capillary imbibition of water in paper sheets [19].…”
Section: Introductionsupporting
confidence: 54%
“…where P is the solid network's effective (compressive) stress. As suggested previously, 15,16,27,28,32 we take the latter to be given by the viscoplastic constitutive law,…”
Section: Two-phase Modelingmentioning
confidence: 99%
“…Moreover, a number of recent studies have suggested that the solid stress must be rate-dependent in order to reproduce the observed dewatering and flow-induced compaction of pulp suspensions and capillary rise through paper sheets. 15,27,28 These studies have accounted for this rate dependence by extending the description of the solid stress to include an effective bulk viscosity of the network, with some precedence existing in earlier work, 16,26,[29][30][31][32] or by analogy with the generic shear viscosity expected for a two-phase medium 33 (alternative perspectives and models also exist 34 ). Thus, pulp suspensions appear to require an unconventional viscoplastic solid stress.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the matrix properties, in particular r 0 , relies on volumetric nitrogen sorption isotherms performed at 77 K. [48] The relatively low porosity along with the high elastic modulus of the silica glass renders any liquid-uptake-induced mechanical deformation negligible [66], in the sub-percent range. Any impact of swelling or contraction, which in principle could affect the imbibition process significantly [67] can thus be ignored.…”
Section: Porous Glass Substratesmentioning
confidence: 99%